Blueprint : Centipede Shoe Rack / Muhammad Hafiz Azizan ...[et al.] - Azizan, Muhammad Hafiz; Mohammad Rosdi, Mohammad Hafiz Asyraf; Muhamad Hatta, Hafidzatun Azwa; Zaini, Kiki Camerena; Mokhtar Rodi, Ezza Suraya (2019)
In the era of technological advancement, most of the people nowadays are tempting to cope with all changes of technology from time to time. Nowadays, based on the survey stated that 73% of the car user in Kola Bharu store shoes in the car. The problem may face by the car user is the shoes is disperse away and bad odor in the car also is present. Centipede Shoe Rack have the solution to overcome this problem such as the product is small in size and easy to compress and stretch. The product also contains mini air humidifier to reduce the bad odor that produce from the shoes. The extra features of the product is have the extra space to store the socks. Based on the survey of concept testing shows that 93.33% of the respondents say that the product is good and majority of the respondent assume that Centipede Shoe Rack is interesting product. The features of the product is attractive, easy to use and keep, protective and odorless based on the concept testing that had been conducted to the respondents. Overall, Centipede Shoe Rack is an efficient product that extension from the standard shoe rack and suitable to use especially for the white collar, lecturer and university students.